Pengamanan Data Akademik Berbasis Web dengan Enkripsi AES-256 (Studi Kasus pada Pendataan Digital SMA XYZ) - Hayat Arka Putri, Zahrah; Arye Yustraini, Yessay; Ariansyah, Ramdhan; Nisa, Najma Choirun; Dyar Wahyuni, Eka; Brastama Putra, Agung (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 3 (2025): JNATIA Vol. 3, No. 3, Mei 2025, 2025)
The development of information technology has provided convenience in data management, including in the context of education. However, this convenience also poses new challenges in terms of data security, especially for sensitive academic information that is vulnerable to unauthorized access. This study aims to develop a web-based academic data security system by implementing the AES-256 encryption algorithm in Cipher Block Chaining (CBC) operation mode. This system is designed using the PHP programming language and MySQL database to manage student data such as name, NISN, class, address, gender, religion, and mother's name. The main focus of system development lies in the application of encryption and decryption processes to sensitive data by utilizing the openssl_encrypt and openssl_decrypt functions, combined with the use of 256-bit encryption keys and random Initialization Vector (IV) to ensure data security. Encrypted data is stored in base64 format to ensure compatibility with relational storage and database systems. Testing is carried out to evaluate the effectiveness of encryption and the accuracy of decryption, as well as to assess its impact on system performance. The results of the study indicate that the system is able to protect sensitive data effectively; information stored in the database cannot be read directly, but can be restored intact if processed by the system with the right key and IV. With a simple interface design and automatic encryption integration, this system is proven to be able to improve the security of academic data without reducing operational efficiency. These findings indicate that the AES-256-CBC encryption approach can be implemented in real education information systems as a practical and reliable security solution.